SM9-based device-friendly distributed decryption scheme for IoHT - Li, Longjiao; Lai, Jianchang; Chen, Liquan; Zhao, Zhen; Wu, Ge; Yang, Xinyan (Computer standards and interfaces, 2026)
IoHT is a specific application of IoT technology in the healthcare field, which enhances medical efficiency and quality. Ensuring secure data sharing among multiple parties is crucial in the IoHT, particularly for resource-constrained devices. As a Chinese national standard and an ISO/IEC standard, SM9 algorithm has been widely applied in IoT, finance, e-government and so on. Although existing SM9-based schemes can ensure data security during multi-party sharing, their high computational overhead makes them unsuitable for lightweight devices. To address this issue, this paper proposes an efficient distributed decryption scheme based on SM9. The proposed scheme achieves secure and efficient multi-party data sharing. And the proposed scheme is very friendly to lightweight devices, as it avoids computationally expensive operations such as bilinear pairing. Based on the q-BDHI assumption, the proposed scheme is proven to be CCA-secure. Finally, we implement our scheme through experiments and the results show that when the number of users reaches 100, the decryption time on resource-constrained devices is about 6 ms, demonstrating that the proposed scheme is suitable for deployment in IoHT. •We propose an efficient distributed identity-based decryption scheme for IoHT.•Our scheme requires only pairing-free operations on lightweight devices.•The scheme resists lazy doctors by ensuring all decryption shares are computed.